Assessing Receiver Performance in Interference-Aware Environments with Channel Estimation Error Considerations (International Journal of Food and Nutritional Sciences, 2021)
We consider the backdrop of uncorrelated Rayleigh flat fading channels and introduce a model that characterizes estimation errors as independent complex Gaussian random variables. By delving into this context, we derive an upper bound on the pairwise error probability (PEP). Most intriguingly, our analysis reveals that the interference-aware receiver maintains full diversity even in the presence of channel estimation errors, further accentuating its robustness. To provide a holistic comparison, we contrast the performance of the interference-aware receiver with that of the MMSE (Minimum Mean Squared Error) receiver. Our findings underscore a notable disparity: the degradation in the performance of the MMSE receiver significantly surpasses that of the interference-aware receiver in scenarios involving imperfect CSI..